Dampak Konflik Peran Ganda dan Work Life Balance terhadap Motivasi Kerja Wanita Pekerja dengan Status Mahasiswa - Zulkarnain Ilyas Idris Zul; Wiwin L. Husin; Poppy Mu'Jizat (Jurnal Ilmu Manajemen, 2025)
Dual role conflict becomes a threat to household life if working women prioritize work outside the home compared to taking care of the household. It is also important to pay attention to the work life balance in the household as a concern for working women. The purpose of this study was to see the impact of dual role conflict and work life balance on the work motivation of working women with student status in Gorontalo Province. The analysis method used was multiple regression analysis. The population in the study was not yet known so that the sampling technique used nonprobability sampling type of purposive sampling where samples were taken based on certain criteria so that the number of samples was 97 respondents. The results of the study showed that partially there was a positive and significant impact of dual role conflict and work life balance on work motivation and simultaneously there was also a positive and significant impact of dual role conflict and work life balance on the work motivation of working women with student status in Gorontalo Province.